1999
DOI: 10.1002/jlb.65.5.700
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JAK2, but not PI 3-kinase/Akt and MAP kinase pathways, in anti-apoptotic signals of GM-CSF in human eosinophils

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) transmits anti-apoptotic signals in eosinophils and is involved in tissue eosinophilia at the site of allergic inflammation. We determined whether phosphatidylinositol 3-kinase (PI 3-kinase) and mitogen-activated protein kinase (MAP kinase) are involved in anti-apoptotic signals of GM-CSF in eosinophils. GM-CSF phosphorylated Akt, a downstream component of PI 3-kinase, and MAP kinases (ERK1 and ERK2) at 10 min after stimulation in eosinophils. GM-CSF pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 49 publications
4
44
0
Order By: Relevance
“…Previous studies using blood eosinophils have reported conflicting data on whether the Ras-Raf-MEK-ERK pathway is important in eosinophil survival. Based on the use of a chemical inhibitor of MEK 1 (PD98059), a previous study by Miike et al 37 reported that ERK activity is not necessary for IL-5-stimulated blood eosinophil survival, and we have recapitulated those data ( Figure 8). Another study has implicated c-Raf-1 as important in eosinophil-mediated survival but not in ERK activation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies using blood eosinophils have reported conflicting data on whether the Ras-Raf-MEK-ERK pathway is important in eosinophil survival. Based on the use of a chemical inhibitor of MEK 1 (PD98059), a previous study by Miike et al 37 reported that ERK activity is not necessary for IL-5-stimulated blood eosinophil survival, and we have recapitulated those data ( Figure 8). Another study has implicated c-Raf-1 as important in eosinophil-mediated survival but not in ERK activation.…”
Section: Discussionsupporting
confidence: 75%
“…A comparable concentration of Tat-GFP protein did not inhibit IL-5-mediated survival during the same period of time, again revealing the selectivity of Tat-dn-H-Ras. In addition, as previously reported, 37 the MEK 1 antagonist PD98059 did not inhibit IL-5-mediated survival. These data demonstrate for the first time that the entire Ras-Raf-MEK-ERK pathway is critical in regulating eosinophil survival and that this may be in part due to the activation not only of Raf-1 but of ERK 1 and ERK 2.…”
Section: Effects Of Blocking the Ras-raf-mek-erk Pathway On Il-5-medisupporting
confidence: 83%
“…35,48 However, the PI3K and MAPK pathways were reported to play no major role for GM-CSF-mediated inhibition of apoptosis in human peripheral blood eosinophils and murine airway eosinophils. 49,50 In contrast, PI3K was involved in prevention of apoptosis in murine eosinophils isolated from the pleural cavity of allergic mice. 51 Similar effects were observed after engagement of b-adrenergic receptors on murine eosinophils, and this process appeared to be mediated by inhibition of the transcription factor forkhead in rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Con¯icting results regarding the role of MEK/ MAPK in preventing apoptosis have emerged these last years (Kinoshita et al, 1995(Kinoshita et al, , 1997Miike et al, 1999;Scheid and Duronio, 1998). Recently, it has been shown that the MEK inhibitor PD98059 did not prevent the IL-3-or GM-CSF-mediated survival of MC/9 cells but reduced Bad phosphorylation (Scheid and Duronio, 1998).…”
Section: Discussionmentioning
confidence: 99%